BnDGAT1s Function Similarly in Oil Deposition and Are Expressed with Uniform Patterns in Tissues of Brassica napus - Zhao, Cuizhu; Li, Huan; Zhang, Wenxue; Wang, Hailan; Xu, Aixia; Tian, Jianhua; Zou, Jitao; Taylor, David C.; Zhang, Meng (Frontiers in Plant Science, 2017)
As an allotetraploid oilcrop, Brassica napus contains four duplicated Acyl-CoA:diacylglycerol acyltransferase 1 (DGAT1) genes, which catalyze one of the rate-limiting steps in triacylglycerol (TAG) biosynthesis in plants. While all four BnDGAT1s have been expressed functionally in yeast, their expression patterns in different germplasms and tissues and also consequent contribution to seed oil accumulation in planta remain to be elucidated. In this study, the coding regions of the four BnDGAT1s were expressed in an Arabidopsis dgat1 mutant. All four BnDGAT1s showed similar effects on oil content and fatty acid composition, a result which is different from that observed in previous studies of their expression in yeast. Expression patterns of BnDGAT1s were analyzed in developing seeds of 34 B. napus inbred lines and in different tissues of 14 lines. Different expression patterns were observed for the four BnDGAT1s, which suggests that they express independently or randomly in different germplasm sources. Higher expression of BnDGAT1s was correlated with higher seed oil content lines. Tissue-specific analyses showed that the BnDGAT1s were expressed in a uniform pattern in different tissues. Our results suggest that it is important to maintain expression of the four BnDGAT1s for maximum return on oil content.